Applying behavioral theory to understand fertility consultation uptake after cancer. Issue 4 (27th February 2019) - Gorman, Jessica R.; Drizin, Julia H.; Mersereau, Jennifer E.; Su, H. Irene
Abstract: Objective: The objective of this study was to examine the association between theoretical constructs from the Health Belief Model and fertility consultation status after cancer. Methods: Reproductive‐aged female cancer survivors self‐reported their use of fertility consultation, perceived severity of and susceptibility to infertility, perceived barriers to and effectiveness of fertility consultation, and cues to action from family/peers and doctors, as well as demographics and cancer characteristics. Logistic regression was used to analyze the association between theoretical constructs and fertility consultation status. Results: Fertility consultation uptake was more prevalent among survivors with higher incomes, those without children, those who wanted a (another) child, and those who were diagnosed more recently. In the final multivariate model, higher perceived severity of infertility, fewer perceived barriers to fertility consultation, and more cues to action from family/peers and doctors were significantly associated with fertility consultation uptake, controlling for income. Exploratory bivariate analyses of barriers to fertility consultation revealed that cost and trouble accessing services were significantly associated with not having a fertility consultation. Conclusions: The Health Belief Model is useful for understanding factors associated with fertility consultation uptake. Efforts should be made to reduce financial barriers and improve patient‐centered assessment of family‐building goals.